2007
DOI: 10.1177/0044118x07301956
|View full text |Cite
|
Sign up to set email alerts
|

School Discipline and Security

Abstract: Prior research finds that racial and ethnic minority students are more likely than White students to receive school punishments, yet little prior research considers students' perceptions of the fairness of school rules and their enforcement. Using data from a nationally representative survey of students, the authors consider whether African American and Latino and Latina students, and particularly males, perceive school safety practices as less fair overall, less well communicated, and less evenly applied than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 25 publications
(36 reference statements)
8
87
3
1
Order By: Relevance
“…Yet, what is surprising is the belief bond (a measure of students' perception in the fairness of the school rules, classroom policies and consequences for breaking rules) is a mediator, or intervening variable, in the relationship between the affiliation bond and student classroom misconduct. The current results extend the prior research citing the role of fair and consistent discipline policies in reducing student misbehaviour (Kupchik and Ellis 2008;Luiselli et al 2005) and demonstrate that students' perception of the "discipline system" as fair has a measurable effect on lowering levels of school misconduct.…”
Section: Discussionsupporting
confidence: 79%
“…Yet, what is surprising is the belief bond (a measure of students' perception in the fairness of the school rules, classroom policies and consequences for breaking rules) is a mediator, or intervening variable, in the relationship between the affiliation bond and student classroom misconduct. The current results extend the prior research citing the role of fair and consistent discipline policies in reducing student misbehaviour (Kupchik and Ellis 2008;Luiselli et al 2005) and demonstrate that students' perception of the "discipline system" as fair has a measurable effect on lowering levels of school misconduct.…”
Section: Discussionsupporting
confidence: 79%
“…Second, it is important to ensure that rules and enforcement are perceived as appropriate and fair by all students. For example, Kupchik and Ellis (2008) found that Black students, compared with White students, are less likely to perceive school rules as fair and school rules and enforcement as appropriate. Third, scholars caution against creating a jaillike, heavily structured environment.…”
Section: Implications For School Policy and Practicementioning
confidence: 99%
“…Pupils must not feel wronged because of their being members of a different group (Kupchik & Ellis, 2008). They should be treated equally into the school.…”
Section: Multiculturalism and School Leadershipmentioning
confidence: 99%